2016
DOI: 10.5966/sctm.2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Potential of Human Bone Marrow-Derived Mesenchymal Stem Cells in Chondrocyte Brick-Enriched Constructs Promoted Stable Regeneration of Craniofacial Cartilage

Abstract: Craniofacial deformities caused by congenital defects or trauma remain challenges for clinicians, whereas current surgical interventions present limited therapeutic outcomes. Injection of bone marrow‐derived mesenchymal stem cells (BMSCs) into the defect is highly desirable because such a procedure is microinvasive and grafts are more flexible to fill the lesions. However, preventing hypertrophic transition and morphological contraction remain significant challenges. We have developed an “all host derived” cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Currently, exosomes have been identified as the principal agent in mediating the therapeutic efficacy of the cell-based regenerative medicine approach [ 20 , 21 , 57 , 58 ], and BMSC-Exos have been reported for promoting in situ cartilage defect repair [ 21 , 26 ]. However, the therapeutic outcome for subcutaneous cartilage defect repair is still limited because of the lack of a suitable pro-chondrogenic environment [ 17 , 40 , 59 ]. Meanwhile, previous studies have also shown that chondrocytes could steer the chondrogenesis of stem cells in vitro and in vivo through paracrine effects [ 1 , 7 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, exosomes have been identified as the principal agent in mediating the therapeutic efficacy of the cell-based regenerative medicine approach [ 20 , 21 , 57 , 58 ], and BMSC-Exos have been reported for promoting in situ cartilage defect repair [ 21 , 26 ]. However, the therapeutic outcome for subcutaneous cartilage defect repair is still limited because of the lack of a suitable pro-chondrogenic environment [ 17 , 40 , 59 ]. Meanwhile, previous studies have also shown that chondrocytes could steer the chondrogenesis of stem cells in vitro and in vivo through paracrine effects [ 1 , 7 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after the addition of BMSC-Exos, expression of SDF-1 and VEGF is upregulated, which promotes cell homing and angiogenesis. This is beneficial for cartilage engineering during the early stage of implantation [ 40 ], which may account for the better neo-cartilage formation in the BMSC-Exos, as reported [ 21 , 26 ]. However, it also has a disadvantage as evidenced by promoting associated ectopic cartilage hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells may be obtained from various tissues, including bone marrow and fat ( 9 ). Bone marrow-derived stem cells are widely used in medical fields in applications including the regeneration of cartilage tissue ( 9 , 10 ). Adipose tissue is suggested to be an abundant and accessible source of adult mesenchymal stem cells ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs have been extensively studied [ [39] , [40] , [41] , [42] ], and a number of scholars are committed to their application in cartilage regeneration. BMSCs have been demonstrated to have immunomodulatory properties, multilineage potential [ 43 ] and tissue homing properties.…”
Section: Overview Of the Advantages Of Microcarriers In The Treatmentmentioning
confidence: 99%